Penerapan Pendekatan Saintifik Model Pembinaan CLCK (Contoh, Latihan, Control, Kerja Mandiri) Siswa Kelas V SD - Sairah Sairah (Jurnal Pendidikan dan Pembelajaran Sekolah Dasar (JPPSD), 2022)
The purpose of this study was to find out how much students' understanding and mastery after the application of the CLCK Guidance Model Scientific Approach (Example, Practice, Control, Independent Work) of Class V Semester I UPT SDN I Palanro, Mallusetasi District, Barru Regency. The research method used is to use a classroom action research model, which is in the form of a spiral from one cycle to the next. Each cycle includes planning (plan), action (action), observation (observation), and reflection (reflection). Based on the results of the research and discussion, it can be concluded that the use of the CLCK Coaching Model (Example, Exercise, Control, Independent Work) can improve students' skills in subject matter which has a positive impact on improving student achievement as indicated by an increase in student learning completeness in each cycle, namely cycle I ( 63.25%), cycle II (78.25%), cycle III (84.75%), with the level of application of a scientific approach to the jigsaw learning model can be shown to increase the value from cycle I to cycle II by 1.50%, while from cycle II to cycle III of 6.50%.